2013
DOI: 10.1007/s00262-013-1461-3
|View full text |Cite
|
Sign up to set email alerts
|

AE37 peptide vaccination in prostate cancer: a 4-year immunological assessment updates on a phase I trial

Abstract: In our recent phase I trial, we demonstrated that the AE37 vaccine is safe and induces HER-2/neu-specific immunity in a heterogeneous population of HER-2/neu (+) prostate cancer patients. Herein, we tested whether one AE37 boost can induce long-lasting immunological memory in these patients. Twenty-three patients from the phase I study received one AE37 boost 6-month post-primary vaccinations. Local/systemic toxicities were evaluated following the booster injection. Immunological responses were monitored 1-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…A detailed description of the phase I clinical trial (EudraCT 2006-003299-37) design has been reported recently [20,21]. In brief, androgen-dependent and androgen-independent prostate cancer patients with primary tumors expressing HER-2/neu + (score 1+ to 3+) and ECOG 0 or 1, were eligible.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the phase I clinical trial (EudraCT 2006-003299-37) design has been reported recently [20,21]. In brief, androgen-dependent and androgen-independent prostate cancer patients with primary tumors expressing HER-2/neu + (score 1+ to 3+) and ECOG 0 or 1, were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve of these patients developed increased immunity in response to AE37 vaccinations and were classified as high responders (HR) (Table 1 and [20,21]). Interestingly, of the 12 HR patients, nine (75 %) were HLA-DRB1*11 positive (+) and seven (58 %) were HLA-A*24+ (Table 1).…”
Section: Association Between Expression Of Two Hla Antigens and Clinimentioning
confidence: 99%
See 2 more Smart Citations
“…AE37 induced strong immunological responses in vivo (delayed-type hypersensitivity) and in vitro (IFNγ production) and it could be measured in majority of the patients. Long-term immunity to AE37 was still detectable 6 months post-vaccinations, and it could be considerably prolonged for an additional period of 36 months after one single booster AE37 injection [71][72][73]. AE37 has also been utilised to vaccinate breast cancer patients in a randomised phase II trial.…”
Section: The Ae37 Therapeutic Cancer Vaccine Paradigmmentioning
confidence: 99%